Performance Evaluation of Sugarcane Grab Loader - กาลศิริศิลป์, รุ่งเรือง; เนตรภักดี, อิศราภรณ์; ลังกาพินธุ์, จตุรงค์ (Frontiers in Engineering Innovation Research, 2018)
Research project entitled performance evaluation of sugarcane grab loader was aimed to study the working capacity and economic analysis of the machine. Three types of sugar cane grab loader were used in this study namely, front end loader, rear end loader and three wheels self-propelled grab loader, respectively. The key performance indicator were working capacity, fuel consumption, percent of the contaminants, break-even point and payback period. Based on the test results the working capacity of the three type of machine was 30, 32 and 39 ton/hr, respectively and the fuel consumption was 14.8, 10 and 11 l/hr, respectively. The percent contaminants was found to be 4, 3 and 3, respectively. The economic analysis showed that the break-even point of the machine was 1959, 2005 and 9425 tons/year, respectively. The operation cost of the machine was 36, 29 and 32 Baht/ton, respectively. Considering the working hour per year of the machine as 500, the payback period of the three type of machine was found to be 0.95, 0.91 and 4.1 year, respectively.